1986
DOI: 10.1002/art.1780290215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by cyclosporin A of streptococcal cell wall‐induced arthritis and hepatic granulomas in rats

Abstract: We investigated the effect of cyclosporin A, an inhibitor of T helperhnducer lymphocyte activation, on the dtwelopment of streptococcal cell wall-induced arm thritis and hepatic granulomas in female LEW/N rats. Continuous daily treatment with cyclosporin A, begun either 24 hours before or 7-12 days after streptococcal cell wall administration and continued for 6 weeks, resulted in significant inhibition of the chronic proliferative, erosive synovitis and total inhibition of hepatic granuloma formation. When cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 22 publications
3
37
1
1
Order By: Relevance
“…Evaluation of lymphocyte function at various time points after SCW administration revealed that within 18 h the proliferative response was suppressed . This immune-deficient state continued through the development of acute arthritic symptoms (days [3][4][5] and persisted during the evolution of the chronic erosive joint lesions (>3 wk) (Fig. 2).…”
Section: Resultsmentioning
confidence: 93%
“…Evaluation of lymphocyte function at various time points after SCW administration revealed that within 18 h the proliferative response was suppressed . This immune-deficient state continued through the development of acute arthritic symptoms (days [3][4][5] and persisted during the evolution of the chronic erosive joint lesions (>3 wk) (Fig. 2).…”
Section: Resultsmentioning
confidence: 93%
“…However, functional T lymphocytes have been shown to play a pivotal role in suseeptibility to SCWinduced, chronic joint inflammation; there even is evidence that SCW-specific T cells are required [3][4][5][6][8][9][10][11]17], Thus, an answer to the question why T cells from F344 rats do not respond to SCW after priming with cell walls might elucidate the mechanism of resistance to SCW arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Dependent on the SCW batch used, either biphasic disease or only the chronic phase may be seen, Thymectomized [3,4], cyclosporin A-treated [4,5] or nude Lewis rats [6], as well as F344 rats [7] are resistant to the second, destructive episode of inflammation, whereas they undergo the acute phase with comparable severity to the Lewis rat. Together, these data strongly suggest an absolute dependence on functional T lymphocytes of the ehronic phase of SCW-induced arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Arthritis was uniformly detected in control cohorts by day 11. Clinical scoring of arthritis was performed as described (22). The distal parts of the fore-and hindlimbs of each animal were graded for swelling on a score of 0-4, ranging from none to maximal involvement.…”
Section: Methodsmentioning
confidence: 99%